Exploring Modality Switching Effects in Negated Sentences: Further Evidence for Grounded Representations - Hald, Lea; Hocking, Ian; Vernon, David; Marshall, Julie-Ann; Garnham, Alan (Frontiers in Psychology, 2013)
Theories of embodied cognition (e.g., Perceptual Symbol Systems Theory; Barsalou, 1999, 2009) suggest that modality-specific simulations underlie the representation of concepts. Supporting evidence comes from modality switch costs: Participants are slower to verify a property in one modality (e.g., auditory, BLENDER-loud) after verifying a property in a different modality (e.g., gustatory, CRANBERRIES-tart) compared to the same modality (e.g., LEAVES-rustling, Pecher, Zeelenberg, & Barsalou, 2003). Similarly, modality switching costs lead to a modulation of the N400 effect in event related potentials (ERPs) (Collins, Pecher, Zeelenberg, & Coulson, 2011; Hald, Marshall, Janssen, & Garnham, 2011). This effect of modality switching has also been shown to interact with the veracity of the sentence (Hald, et al., 2011). The current event-related potentials study (ERPs) further explores the role of modality match/mismatch on the processing of veracity as well as negation (sentences containing “not”). Our results indicate a modulation in the ERP based on modality and veracity, plus an interaction. The evidence supports the idea that modality-specific simulations occur during language processing, and furthermore suggest that these simulations alter the processing of negation.